Diasporic experiences portrayed in Luling character as the first-generation in Amy Tan's The Bonesetter's Daughter - Septiarini Makodamayanti; Diyah Fitri Wulandari (EduLite: Journal of English Education, Literature and Culture, 2019)
This study deals with the issue of diaspora which relates to diasporic experiences as well as the impact of diaspora. The research attempted to find out the experiences encountered by LuLing and to know the impact of diaspora perceived by her as the analyzed character, during her process of diaspora. Descriptive Qualitative research was used in the arranging of this undergraduate thesis. The data came from various sources that were classified into primary data and secondary data. The primary data were taken from the Bonesetter's Daughter novel by Amy Tan. The secondary data were taken from book, printed and online journals and articles. The first step for analyzing the data was by reading the whole chapters of the Bonesetter's Daughter novel. While the second step, was underlining or highlighting the parts that showed about the diasporic experiences and the impact of diaspora encountered by LuLing. This study shows how the phenomenon of diaspora invokes some experiences and gives an impact to the diasporas as reflected in the Bonesetter's Daughter novel. The movement of LuLing to America triggered by the war in her country had allowed her to undergo some experiences like acculturation, culture shock, and separation, along with the psychological impact of the movement that she had. Through LuLing, the Chinese first-generation woman character, this novel shows how the Chinese diasporas live their life in a country which is different from their homeland.